Discovering Ways That Influence the Older Nurse to Continue Bedside Practice. (28th April 2011) - Spiva, LeeAnna; Hart, Patricia; McVay, Frank
Abstract : A descriptive qualitative approach was used to investigate older nurses practicing bedside nursing and to identify ways to influence older nurses to continue bedside practice. A purposive sample of 18 older nurses was recruited from a healthcare system located in the Southeastern United States. Interpretative analysis of interviews resulted in the identification of three constitutive patterns and eight themes. The first constitutive pattern identified was attributes of the older nurse. The themes comprising this pattern were (a) professional growth in confidence and skills through experience and (b) passion and love for nursing. The second constitutive pattern was enduring stress and frustration. The themes comprising this pattern were (a) physical and mental changes associated with aging, (b) increased patient acuity and patient load, (c) constant change, and (d) time constraints. The third constitutive pattern was enhancements needed for older nurses to continue bedside nursing. The themes comprising this pattern were (a) work environment enhancements and (b) organizational relationship enhancements. Findings may provide a better understanding of the older nurse's role in bedside nursing.